IMPLEMENTACIÓN DE LAS TIC EN REPÚBLICA DOMINICANA. ACERCAMIENTO A LA PERCEPCIÓN DE LOS DOCENTES - Wiselis-Rosanna SENA-RIVAS (Fonseca, Journal of Communication, 2023)
The main objective of this research is to investigate teachers’ perception of the EDPJA program in the Dominican Republic, as well as their opinion on ICT training. Likewise, it analyzes, the possibilities that represent the means of technology of the information and communication; in addition, it develops an analysis on the role of ICT in the work rooms, in the same way that influences the teaching-learning processes and the possible technical difficulties that can be generated. From a quantitative study with a non-experimental-transverse exploratory type design